Concurrent Multidrug-Resistant Pseudomonas aeruginosa and Klebsiella pneumoniae subsp. Pneumoniae Infections in a 3-year-old Domestic Shorthair Cat in Pekanbaru, Riau, Indonesia: A Case Report - Rifia Fani; Tito Suprayoga (Media Kedokteran Hewan, 2026)
Multidrug-resistant Gram-negative bacterial infections, especially those caused by Klebsiella pneumoniae and Pseudomonas aeruginosa, are becoming a problem in veterinary medicine. There are still not many reports of cats having multiple multidrug-resistant infections at the same time, especially in Indonesia. This case report presents a 3-year-old male domestic shorthair cat with chronic purulent nasal discharge, dyspnea, and tachycardia, unresponsive to empirical antibiotic treatment with amoxicillin–clavulanic acid. Thoracic radiography showed that both lungs had increased opaque. Nasal swab samples from both nostrils were cultured on blood agar, MacConkey agar, and desoxycholate agar. We used an automated system (bioMérieux VITEK® 2 Compact) to identify the bacteria and test their susceptibility to antibiotics by determining the minimum inhibitory concentration. Pseudomonas aeruginosa and Klebsiella pneumoniae subsp. pneumoniae, both exhibiting resistance to various antimicrobial classes, including β-lactams, aminoglycosides, fluoroquinolones, sulfonamides, and monobactams. Both isolates were sensitive to meropenem. Targeted therapy with intravenous meropenem (5 mg/kg body weight, twice a day for 10 days) led to clinical improvement of respiratory symptoms and radiographic improvement. This case highlights the significance of culture-based diagnostics and antimicrobial susceptibility testing in the management of multidrug-resistant co-infections in felines.